Asymptotic behavior of the coefficients of solutions of the Hill equation - Kochmanski, S.; Кохманьски, С. (Institute of Mathematics, NAS of Ukraine, 1994)
A new method for finding the asymptotics of the coefficients of solutions of the Hill equation is given.